Accuracy of Stellar Mass-to-light Ratios of Nearby Galaxies in the Near Infrared - Taehyun Kim; Minjin Kim; Luis C. Ho; Yang A. Li; Woong-Seob Jeong; Dohyeong Kim; Yongjung Kim; Bomee Lee; Dongseob Lee; Jeong Hwan Lee; Jeonghyun Pyo; Hyunjin Shim; et al. (The Astronomical Journal)
Future satellite missions are expected to perform all-sky surveys, thus providing the entire sky near-infrared spectral data and consequently opening a new window to investigate the evolution of galaxies. Specifically, the infrared spectral data facilitate the precise estimation of stellar masses of numerous low-redshift galaxies. We utilize the synthetic spectral energy distribution (SED) of 2853 nearby galaxies drawn from the DustPedia (435) and Stripe 82 regions (2418). The stellar mass-to-light ratio ( M _* / L ) estimation accuracy over a wavelength range of 0.75−5.0 μ m is computed through the SED fitting of the multiwavelength photometric data set, which has not yet been intensively explored in previous studies. We find that the scatter in M _* / L is significantly larger in the shorter and longer wavelength regimes due to the effect of the young stellar population and the dust contribution, respectively. While the scatter in M _* / L approaches its minimum (∼0.10 dex) at ∼1.6 μ m, it remains sensitive to the adopted star formation history model. Furthermore, M _* / L demonstrates weak and strong correlations with the stellar mass and the specific star formation rate (SFR), respectively. Upon adequately correcting the dependence of M _* / L on the specific SFR, the scatter in the M _* / L further reduces to 0.02 dex at ∼1.6 μ m. This indicates that the stellar mass can be estimated with an accuracy of ∼0.02 dex with a prior knowledge of SFR, which can be estimated using the infrared spectra obtained with future survey missions.